Who needs market information? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
THE KEY PLAYERS Group Short-term Long-term Existing sources Farmers Market Structure Prices, Sales, Quality ...